Female body mass index and the selection of a long‐acting reversible contraception for the first time. Issue 3 (5th January 2022) - Frederico, Giulia; Silva dos Santos, Priscilla N.; Ferreira, Jéssica M.; Bahamondes, Luis; Fernandes, Arlete
Abstract: Objective: To evaluate Brazilian women with different body mass index (BMI, calculated as weight in kilograms divided by the square of height in meters) values who were switching from a short‐acting reversible contraceptive (SARC) to a long‐acting reversible contraceptive (LARC) method in relationship to the reasons reported for switching and the LARC method chosen. Method: We analyzed retrospective data from 1508 women aged 18–49 years who chose a LARC for the first time. The variables were sociodemographic, BMI, SARC in use, the reason given for switching, the chosen LARC (copper intrauterine device, levonorgestrel (52 mg) intrauterine system or ethyl norgestrel implant), and expectations of the LARC. We used χ 2, Mann‐Whitney, and Kruskal‐Wallis tests to compare BMI groups. The significance level adopted was 5%. Results: The obesity group, 320 women (21.2%), reported weight gain ( P  < 0.000) and fear of pregnancy ( P  = 0.004) as the most frequent reasons for switching, whereas the normal weight group, 637 women (42.2%), reported more loss of libido ( P  < 0.000) and other personal complaints ( P  = 0.002). The IUD was chosen by 851 women (56.6%) and significantly by the largest number of obese women. Conclusion: Women in different BMI categories report different reasons for switching from SARC methods and elect different LARC methods for contraception. Abstract : Women in different BMI categories report different reasons for switching from short‐acting reversible contraception and choosing different long‐acting reversible contraception methods.